2021
DOI: 10.1155/2021/3055722
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Corneal Parameters after DMEK Surgery: A Swept-Source Imaging Analysis at 12-Month Follow-Up Time

Abstract: Purpose. To assess the time course changes in corneal topographic parameters during the one-year follow-up after Descemet membrane endothelial keratoplasty (DMEK) surgery. Materials and Methods. Twenty-one patients (24 eyes) who underwent DMEK surgery were evaluated. Best corrected visual acuity (BCVA), endothelial cell count (ECC), central corneal thickness (CCT), mean keratometry (MK), mean astigmatism (MA), astigmatism asymmetry (AA), and higher-order aberration (HOA) were assessed at baseline and 1, 3, 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Our failure to find a correlation between preoperative CCT and post-DMEK BSCVA has also been observed by three other studies, including two with large cohorts (n = 160 and 1084) [14,15,21]. However, a study by Peraza-Nieves et al on 393 DMEK eyes found with multivariate analysis that 1-μm higher preoperative CCT predicted 0.0008 higher logMAR BSCVA at 24 months [6].…”
Section: Correlation Between Postoperative Cct and 12-month Bscvasupporting
confidence: 80%
See 2 more Smart Citations
“…Our failure to find a correlation between preoperative CCT and post-DMEK BSCVA has also been observed by three other studies, including two with large cohorts (n = 160 and 1084) [14,15,21]. However, a study by Peraza-Nieves et al on 393 DMEK eyes found with multivariate analysis that 1-μm higher preoperative CCT predicted 0.0008 higher logMAR BSCVA at 24 months [6].…”
Section: Correlation Between Postoperative Cct and 12-month Bscvasupporting
confidence: 80%
“…Thus, it is possible that this CCT threshold could help determine when to conduct DMEK, with the aim of achieving the best possible postoperative visual acuity. However, four other studies have to our knowledge examined the relationship between preoperative CCT and final BSCVA after DMEK, and three failed to find a relationship [6,14,15,21] (Table 1). To address this issue further, we performed the present study assessing the influence of preoperative CCT on the postoperative BSCVA of eyes that underwent DMEK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of the DMEK graft and surgery was performed following the ‘no-touch’ technique, as described previously [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several DMEK tissue injectors have been introduced with narrower tips as surgeons continue their pursuit of more optimal astigmatism outcomes, but surgeons' adoption of narrower DMEK injectors has been mixed. 3,4 One concern is that DMEK tissue will incur greater endothelial cell loss (ECL) in injectors with narrower lumens because the corneal endothelium, which resides on the outside of the scroll, may have more contact with the lumen wall. This contact may especially be greater when the cross-sectional diameter of tissue scroll (ie, scroll width) is greater than the injector lumen diameter.…”
mentioning
confidence: 99%